A special anticorrosive coating for reinforcing steel and a coating method thereof

CN122878809APending Publication Date: 2026-10-09XIAN LIANGLI POWER GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410664490.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但在这些应用中,金属涂料成本较高,环氧树脂涂料会引起钢筋与混凝土的粘结力下降;水性无机涂料孔隙率及脆性较高,限制了其在建筑钢筋中的应用

Benefits of technology

本发明中,通过合理选择原料及各原料成分间的相互配合、协同,使涂料的成膜性好,形成的漆膜的柔韧性、稳定性、抗流挂性、抗冲击性、附着力、耐久性及对盐、酸、碱的耐受性强,可有效提高钢筋的防腐性、抗拉强度、粘结力等,延长钢筋使用寿命。基于此,本发明的防腐涂料具有成本低、力学性能强、防腐效果好等特点。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a special anticorrosive paint for reinforcing steel bars and a coating method thereof, and relates to the technical field of paints.The raw material components and weight fractions of the anticorrosive paint are as follows: 10-15 parts of chlorinated natural latex, 15-20 parts of modified diatomite, 4-8 parts of graphene, 8-12 parts of fiber, 1.0-1.2 parts of feather powder, 4-8 parts of eggshell powder, 0.001-0.003 parts of gadolinium sulfate, 0.2-0.3 parts of polyvinyl alcohol, 16-20 parts of sodium hydroxide solution, 0.04-0.06 parts of calcium hydroxide, 1-3 parts of dispersant, 0.5-1.0 parts of leveling agent, 0.5-1.0 parts of defoaming agent and 4-8 parts of curing agent.The anticorrosive paint has the characteristics of low cost, strong mechanical property and good anticorrosive effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating technology, specifically to a special anti-corrosion coating for steel bars and its application method. Background Technology

[0002] With the rapid development of engineering construction in my country, concrete, especially reinforced concrete, is being used more and more widely in basic engineering projects, playing a vital role in the national economic infrastructure. However, as the use of steel reinforcement in concrete increases, the possibility of steel reinforcement corrosion in concrete is also rapidly increasing due to various environmental factors.

[0003] Applying anti-corrosion coatings to reinforcing bars is an effective method for preventing corrosion. Currently, commonly used anti-corrosion coatings include epoxy resin coatings, galvanized metal coatings, and water-based inorganic coatings. However, among these applications, metal coatings are more expensive, epoxy resin coatings can reduce the bond strength between the reinforcing bar and concrete, and water-based inorganic coatings have higher porosity and brittleness, limiting their application in building reinforcing bars.

[0004] Therefore, it is of great significance to develop a low-cost, high-performance anti-corrosion coating specifically for steel bars. Summary of the Invention

[0005] To address the above-mentioned problems, this invention provides a special anti-corrosion coating for reinforcing bars and its application method.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a special anti-corrosion coating for steel bars. The raw material components and weight parts of the anti-corrosion coating are as follows: 10-15 parts of chlorinated natural latex, 15-20 parts of modified diatomaceous earth, 4-8 parts of graphene, 8-12 parts of fiber, 1.0-1.2 parts of feather powder, 4-8 parts of eggshell powder, 0.001-0.003 parts of gadolinium sulfate, 0.2-0.3 parts of polyvinyl alcohol, 16-20 parts of sodium hydroxide solution (mass concentration 20%), 0.04-0.06 parts of calcium hydroxide, 1-3 parts of dispersant, 0.5-1.0 parts of leveling agent, 0.5-1.0 parts of defoamer, and 4-8 parts of curing agent.

[0007] Further, the modified diatomaceous earth is prepared by adding 20% ​​sodium hydroxide solution to diatomaceous earth, stirring for 6 hours, filtering, then adding acrylic acid, carboxymethyl cellulose, and NN methylenebisacrylamide, mixing evenly, ball milling for 2 hours, then adding ammonium persulfate, water bath at 60°C for 0.5 hours, vacuum drying at 65°C, pulverizing, and passing through a 180-mesh sieve to obtain the modified diatomaceous earth.

[0008] Furthermore, the fibers, by weight, comprise 6-10 parts of ethylene-tetrafluoroethylene copolymer fiber, 4-8 parts of silicon carbide fiber, and 4-8 parts of glass fiber.

[0009] Furthermore, the feather powder has a particle size of 50-75µm, and the eggshell powder has a particle size of 25-40µm.

[0010] Furthermore, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L.

[0011] Further, the dispersant is sodium polyacrylate; the leveling agent is polyether-modified polymethylalkylsiloxane; the defoamer is a polyether ester defoamer; and the curing agent is a polyether amine curing agent or alicyclic amine curing agent.

[0012] This invention also provides a method for applying a special anti-corrosion coating for steel bars, which specifically includes the following steps: S1: Take all raw materials according to the weight proportions and set aside; S2: Mix and stir the modified diatomaceous earth, graphene, and fiber evenly to obtain component A; S3: Mix feather powder, eggshell powder and sodium hydroxide solution, stir evenly, add polyvinyl alcohol, continue stirring evenly, then add gadolinium sulfate and calcium hydroxide, stir at 40-50℃ for 30 minutes to obtain component B; S4: Mix the dispersant, leveling agent, defoamer, and curing agent evenly, add chlorinated natural latex and deionized water, and stir evenly again to obtain component C; S5: Mix components A, B, and C thoroughly and grind them to obtain the anti-corrosion coating for later use; S6: Remove rust from the surface of the reinforcing steel, clean it thoroughly, and dry it to obtain the treated reinforcing steel. S7: Immerse the treated steel bars in the anti-corrosion coating from step S5. After the coating is evenly applied, remove the steel bars, let them stand, and allow them to dry and cure.

[0013] Furthermore, in step S4, the mass ratio of chlorinated natural latex to deionized water is 1:2-3.

[0014] In this invention, chlorinated natural latex is a rubber derivative modified by chlorination of natural rubber. It possesses good flexibility and film-forming properties, exhibiting extremely low permeability to water and oxygen, resistance to common acid and alkali corrosion, high hardness, and good flame retardancy. This improves the adhesion and corrosion resistance of coatings, extending the service life of reinforcing steel. Modification of diatomaceous earth enhances its water absorption, salt resistance, and heat resistance, thereby increasing the plastic viscosity of the coating and inhibiting shrinkage cracking. Ethylene-tetrafluoroethylene copolymer fibers possess corrosion resistance, high and low temperature resistance, and weather resistance; silicon carbide fibers have high strength and high modulus, good heat resistance, oxidation resistance, and chemical stability; glass fibers have high tensile strength, strong impact resistance, and good heat resistance. The alkaline solution causes the proteins in feather powder and eggshell powder to dissociate and the disulfide bonds to break. Under the catalysis of gadolinium sulfate, the hydrophilic groups of the proteins crosslink with polyvinyl alcohol, enhancing hydrophobicity and giving it better film-forming properties. It can be firmly and stably combined with other base materials, forming a smooth paint film with good water resistance. In addition, eggshell powder contains a large amount of calcium carbonate. Ultrafine calcium carbonate has anti-settling and antibacterial effects in coatings, and can also make the coating fine and uniform, and enhance the mechanical properties of the coating.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: In this invention, by rationally selecting raw materials and ensuring the synergistic effect of their components, the coating exhibits excellent film-forming properties. The resulting paint film possesses strong flexibility, stability, anti-sagging, impact resistance, adhesion, durability, and resistance to salts, acids, and alkalis. This effectively improves the corrosion resistance, tensile strength, and adhesion of reinforcing steel bars, extending their service life. Therefore, the anti-corrosion coating of this invention features low cost, strong mechanical properties, and excellent anti-corrosion effect. Detailed Implementation

[0016] To make the objectives and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0017] Unless otherwise specified, the instruments, reagents, and materials used in the following embodiments are all conventional instruments, reagents, and materials already available in the prior art and can be obtained through legitimate commercial channels. Unless otherwise specified, the experimental methods and detection methods used in the following embodiments are all conventional experimental methods and detection methods already available in the prior art.

[0018] Preparation Example 1 Preparation of modified diatomaceous earth: Add 20% sodium hydroxide solution (completely immerse) to 150g of diatomaceous earth, stir for 6h, filter, then add 25g of acrylic acid, 25g of carboxymethyl cellulose, and 0.01g of NN methylenebisacrylamide, mix evenly, ball mill for 2h, then add 1g of ammonium persulfate, water bath at 60℃ for 0.5h, vacuum dry at 65℃, pulverize, and pass through a 180-mesh sieve to obtain modified diatomaceous earth.

[0019] Example 1 This embodiment provides a special anti-corrosion coating for steel bars. The raw material components and weight parts of the anti-corrosion coating are as follows: 10 parts chlorinated natural latex, 15 parts modified diatomaceous earth, 4 parts graphene, 8 parts fiber, 1.0 part feather powder, 4 parts eggshell powder, 0.001 parts gadolinium sulfate, 0.2 parts polyvinyl alcohol, 16 parts sodium hydroxide solution, 0.04 parts calcium hydroxide, 1 part sodium polyacrylate, 0.5 parts polyether modified polymethylalkylsiloxane, 0.5 parts polyether ester defoamer, and 4 parts polyether amine curing agent.

[0020] in: The fibers, by weight, include 6 parts ethylene-tetrafluoroethylene copolymer fiber, 4 parts silicon carbide fiber, and 4 parts glass fiber.

[0021] The feather meal has a particle size of 50µm, and the eggshell meal has a particle size of 25µm.

[0022] The concentration of the sodium hydroxide solution is 0.1 mol / L.

[0023] This embodiment also provides a method for applying a special anti-corrosion coating for reinforcing bars, which specifically includes the following steps: S1: Take all raw materials according to the weight proportions and set aside; S2: Mix and stir the modified diatomaceous earth, graphene, and fiber evenly to obtain component A; S3: Mix feather powder, eggshell powder and sodium hydroxide solution, stir evenly, add polyvinyl alcohol, continue stirring evenly, then add gadolinium sulfate and calcium hydroxide, stir at 40℃ for 30 minutes to obtain component B; S4: Mix the dispersant, leveling agent, defoamer, and curing agent evenly, add chlorinated natural latex and deionized water in a mass ratio of 1:2, and stir evenly again to obtain component C; S5: Mix components A, B, and C thoroughly and grind them to obtain the anti-corrosion coating for later use; S6: Remove rust from the surface of the reinforcing bars to meet the Sa2.5 rust removal standard. Clean the surface thoroughly and dry it to obtain the treated reinforcing bars. S7: Immerse the treated steel bars in the anti-corrosion coating from step S5. After the coating is evenly applied, remove the steel bars, let them stand, and allow them to dry and cure.

[0024] Example 2 This embodiment provides a special anti-corrosion coating for steel bars. The raw material components and weight parts of the anti-corrosion coating are as follows: 12 parts chlorinated natural latex, 18 parts modified diatomaceous earth, 6 parts graphene, 10 parts fiber, 1.1 parts feather powder, 6 parts eggshell powder, 0.002 parts gadolinium sulfate, 0.25 parts polyvinyl alcohol, 18 parts sodium hydroxide solution, 0.05 parts calcium hydroxide, 2 parts sodium polyacrylate, 0.8 parts polyether modified polymethylalkylsiloxane, 0.8 parts polyether ester defoamer, and 6 parts polyether amine curing agent.

[0025] in: The fibers, by weight, include 8 parts ethylene-tetrafluoroethylene copolymer fiber, 6 parts silicon carbide fiber, and 6 parts glass fiber.

[0026] The particle size of feather meal is 60µm, and the particle size of eggshell meal is 35µm.

[0027] The concentration of the sodium hydroxide solution is 0.15 mol / L.

[0028] This embodiment also provides a method for applying a special anti-corrosion coating for reinforcing bars, which specifically includes the following steps: S1: Take all raw materials according to the weight proportions and set aside; S2: Mix and stir the modified diatomaceous earth, graphene, and fiber evenly to obtain component A; S3: Mix feather powder, eggshell powder and sodium hydroxide solution, stir evenly, add polyvinyl alcohol, continue stirring evenly, then add gadolinium sulfate and calcium hydroxide, stir at 45℃ for 30 minutes to obtain component B; S4: Mix the dispersant, leveling agent, defoamer, and curing agent evenly, add chlorinated natural latex and deionized water at a mass ratio of 1:2.5, and stir evenly again to obtain component C; S5: Mix components A, B, and C thoroughly and grind them to obtain the anti-corrosion coating for later use; S6: Remove rust from the surface of the reinforcing bars to meet the Sa2.5 rust removal standard. Clean the surface thoroughly and dry it to obtain the treated reinforcing bars. S7: Immerse the treated steel bars in the anti-corrosion coating from step S5. After the coating is evenly applied, remove the steel bars, let them stand, and allow them to dry and cure.

[0029] Example 3 This embodiment provides a special anti-corrosion coating for steel bars. The raw material components and weight parts of the anti-corrosion coating are as follows: 15 parts chlorinated natural latex, 20 parts modified diatomaceous earth, 8 parts graphene, 12 parts fiber, 1.2 parts feather powder, 8 parts eggshell powder, 0.003 parts gadolinium sulfate, 0.3 parts polyvinyl alcohol, 20 parts sodium hydroxide solution, 0.06 parts calcium hydroxide, 3 parts sodium polyacrylate, 1.0 part polyether modified polymethylalkylsiloxane, 1.0 part polyether ester defoamer, and 8 parts alicyclic amine curing agent.

[0030] in: The fibers, by weight, include 10 parts ethylene-tetrafluoroethylene copolymer fiber, 8 parts silicon carbide fiber, and 8 parts glass fiber.

[0031] The feather meal has a particle size of 75µm, and the eggshell meal has a particle size of 40µm.

[0032] The concentration of the sodium hydroxide solution is 0.2 mol / L.

[0033] This embodiment also provides a method for applying a special anti-corrosion coating for reinforcing bars, which specifically includes the following steps: S1: Take all raw materials according to the weight proportions and set aside; S2: Mix and stir the modified diatomaceous earth, graphene, and fiber evenly to obtain component A; S3: Mix feather powder, eggshell powder and sodium hydroxide solution, stir evenly, add polyvinyl alcohol, continue stirring evenly, then add gadolinium sulfate and calcium hydroxide, stir at 50℃ for 30 minutes to obtain component B; S4: Mix the dispersant, leveling agent, defoamer, and curing agent evenly, add chlorinated natural latex and deionized water in a mass ratio of 1:3, and stir evenly again to obtain component C; S5: Mix components A, B, and C thoroughly and grind them to obtain the anti-corrosion coating for later use; S6: Remove rust from the surface of the reinforcing bars to meet the Sa2.5 rust removal standard. Clean the surface thoroughly and dry it to obtain the treated reinforcing bars. S7: Immerse the treated steel bars in the anti-corrosion coating from step S5. After the coating is evenly applied, remove the steel bars, let them stand, and allow them to dry and cure.

[0034] Comparative Example 1 Epoxy anti-corrosion coating (model HF-01, purchased from Jining Qibao Environmental Protection Technology Co., Ltd.) The coatings of Examples 1-3 and Comparative Example 1 were subjected to the following performance tests: (1) The appearance test of the paint film was carried out in accordance with the visual colorimetric standard of GB / T 9761-88 for paints and varnishes.

[0035] Observation results: The paint film formed on the surface of the sample coated with the anti-corrosion coating of Examples 1-3 all had a smooth and even appearance, while the paint film formed on the surface of the sample coated with the anti-corrosion coating of Comparative Example 1 all showed obvious roughness.

[0036] (2) The storage stability of the coating was tested in accordance with GB / T 6753.3-1986.

[0037] Evaluation results: After opening, the anti-corrosion coatings of Examples 1-3 showed no skin formation or putrid smell. The sedimentation degree was measured with a 100mm long coating tool, and no sedimentation was found. The coatings were unchanged from their original state. The coating of Comparative Example 1 showed slight skin formation and sedimentation.

[0038] (3) The anti-sagging test of the coating shall be conducted in accordance with GB / T 9264-1988 standard (test range: 50-475μm).

[0039] The results showed that the anti-corrosion coating samples of Examples 1-3 did not sag at 315 μm, while the anti-corrosion coating sample of Comparative Example 1 did not sag at 225 μm.

[0040] (4) Impact resistance test shall be conducted in accordance with GB / T 1732-1993 standard.

[0041] The results showed that the impact resistance of the paint film in Examples 1-3 was 48.9-49.5 cm, while that of the paint film in Comparative Example 1 was 45.8 cm. In other words, when a hammer of the same mass falls on the test plate, the maximum height at which the paint film in Examples 1-3 does not cause damage is higher than that in Comparative Example 1. Therefore, the impact resistance of the paint film in Examples 1-3 is better than that in Comparative Example 1.

[0042] (5) The adhesion of the coating shall be tested in accordance with GB / T 9286-1998 standard.

[0043] The results showed that the anti-corrosion coatings of Examples 1-3 had completely smooth edges after cutting, with no peeling off, so their adhesion was grade 0; the peeling of Comparative Example 1 was present, but the peeling rate was less than 5%, so its adhesion was grade 1.

[0044] (6) Water resistance test shall be conducted in accordance with GB / T 1733-1993 standard.

[0045] The water resistance test results showed that the test panels coated with the anti-corrosion coatings of Examples 1-3 showed no rust or blistering after immersion for 90 days. The test panels coated with the anti-corrosion coating of Comparative Example 1 began to show rust after 76 days, and showed small-area rust and blistering after immersion for 90 days.

[0046] (7) Conduct salt water resistance test according to GB / T 9274—1988 standard.

[0047] Salt water resistance test results show that the test panels coated with the anti-corrosion coatings of Examples 1-3 showed no rust or blistering after immersion for 90 days. The test panel of Comparative Example 1 began to show rust after 72 days, and small areas of rust and blistering appeared after immersion for 90 days.

[0048] (8) Salt spray resistance test shall be conducted in accordance with GB / T1771-2007 standard.

[0049] Salt spray resistance test results show that the test panels coated with the anti-corrosion coatings of Examples 1-3 showed no rust or blistering after immersion for 30 days. The test panels coated with the anti-corrosion coating of Comparative Example 1 began to show rust after 17 days, and small areas of rust and blistering appeared after 30 days.

[0050] (9) Conduct chemical corrosion resistance test according to GB 1763-79 standard.

[0051] The results showed that the steel bars coated with the anti-corrosion coatings of Examples 1-3 did not blister or peel off after immersion for 7 days. The test plate coated with the anti-corrosion coating of Comparative Example 1 began to blister after 5 days, and large-area blistering occurred after 7 days.

[0052] (10) Test the bond performance of steel bars according to GB50152-92 Test Methods for Concrete Structures.

[0053] The results showed that the bond strength of the steel bars coated with the anti-corrosion coatings of Examples 1-3 was 4.3-4.7 MPa, that of ordinary steel bars was 2.5 MPa, and that of the steel bars coated with the anti-corrosion coating of Comparative Example 1 was 3.6 MPa. Therefore, the anti-corrosion coatings of Examples 1-3 can significantly improve adhesion.

[0054] In summary, the anti-corrosion coatings of Examples 1-3 have a smooth and even film appearance, and their storage stability, anti-sagging, impact resistance, and adhesion are all superior to those of Comparative Example 1. Furthermore, their water resistance, salt water resistance, salt spray resistance, and chemical corrosion resistance are also significantly better than those of Comparative Example 1. They are anti-corrosion coatings with strong storage stability, strong anti-sagging, strong impact resistance, strong adhesion, and excellent water resistance, salt water resistance, and salt spray resistance, and can be widely used in construction engineering.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A special anti-corrosion coating for reinforcing bars, characterized in that: The raw material components and weight parts of the anti-corrosion coating are as follows: 10-15 parts chlorinated natural latex, 15-20 parts modified diatomaceous earth, 4-8 parts graphene, 8-12 parts fiber, 1.0-1.2 parts feather powder, 4-8 parts eggshell powder, 0.001-0.003 parts gadolinium sulfate, 0.2-0.3 parts polyvinyl alcohol, 16-20 parts sodium hydroxide solution, 0.04-0.06 parts calcium hydroxide, 1-3 parts dispersant, 0.5-1.0 parts leveling agent, 0.5-1.0 parts defoamer, and 4-8 parts curing agent.

2. The anti-corrosion coating for reinforcing bars according to claim 1, characterized in that: The modified diatomaceous earth is prepared by adding 20% ​​sodium hydroxide solution to diatomaceous earth, stirring for 6 hours, filtering, then adding acrylic acid, carboxymethyl cellulose, and NN methylenebisacrylamide, mixing evenly, ball milling for 2 hours, then adding ammonium persulfate, water bath at 60°C for 0.5 hours, vacuum drying at 65°C, pulverizing, and passing through a 180-mesh sieve to obtain the modified diatomaceous earth.

3. The anti-corrosion coating for reinforcing bars according to claim 1, characterized in that: The fibers, by weight, comprise 6-10 parts of ethylene-tetrafluoroethylene copolymer fiber, 4-8 parts of silicon carbide fiber, and 4-8 parts of glass fiber.

4. The anti-corrosion coating for reinforcing bars according to claim 1, characterized in that: The feather powder has a particle size of 50-75µm, and the eggshell powder has a particle size of 25-40µm.

5. The anti-corrosion coating for reinforcing bars according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 0.1-0.2 mol / L.

6. The anti-corrosion coating for reinforcing bars according to claim 1, characterized in that: The dispersant is sodium polyacrylate; the leveling agent is polyether-modified polymethylalkylsiloxane; the defoamer is polyether ester defoamer; and the curing agent is polyether amine curing agent or alicyclic amine curing agent.

7. A method for applying a special anti-corrosion coating for reinforcing bars as described in any one of claims 1-6, characterized in that: Specifically, the steps include the following: S1: Take all raw materials according to the weight proportions and set aside; S2: Mix and stir the modified diatomaceous earth, graphene, and fiber evenly to obtain component A; S3: Mix feather powder, eggshell powder and sodium hydroxide solution, stir evenly, add polyvinyl alcohol, continue stirring evenly, then add gadolinium sulfate and calcium hydroxide, stir at 40-50℃ for 30 minutes to obtain component B; S4: Mix the dispersant, leveling agent, defoamer, and curing agent evenly, add chlorinated natural latex and deionized water, and stir evenly again to obtain component C; S5: Mix components A, B, and C thoroughly and grind them to obtain the anti-corrosion coating for later use; S6: Remove rust from the surface of the reinforcing steel, clean it thoroughly, and dry it to obtain the treated reinforcing steel. S7: Immerse the treated steel bars in the anti-corrosion coating from step S5. After the coating is evenly applied, remove the steel bars, let them stand, and allow them to dry and cure.

8. The method for applying a special anti-corrosion coating for reinforcing bars according to claim 7, characterized in that: In step S4, the mass ratio of chlorinated natural latex to deionized water is 1:2-3.